The Interest of Women with Mayer-Rokitansky-Küster-Hauser Syndrome and Laparoscopic Vecchietti Neovagina in Uterus Transplantation - Chmel, Roman; Novackova, Marta; Pastor, Zlatko; Fronek, Jiri (Journal of pediatric and adolescent gynecology, 2018)
STUDY OBJECTIVE: The goal of this study was to assess a group of women with Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome with surgically created neovaginas in the interest of uterus transplantation (UTx) and to recruit the first group of applicants for a UTx trial. DESIGN AND SETTING: This was an original prospective study using semistructured interviews. PARTICIPANTS: A study group of 50 women with MRKH syndrome with Vecchietti neovaginas was recruited via letter of invitation. INTERVENTIONS AND MAIN OUTCOME MEASURES: Interest of MRKH women in obtaining experimental UTx for the treatment of absolute uterine factor infertility. RESULTS: A total of 50 women responded via e-mail and 31 (62% [31 of 50] of the study group) expressed serious interest in UTx after complete information about its risks and benefits was provided during the first semistructured interview. They subsequently agreed to participate in additional interviews and further examinations. Because of various reasons, only 9 women were prepared to enter our UTx trial (18% [9 of 50] of the study group). Three recipients/donors were accepted into the living donor arm and 6 into the deceased brain donor arm of the trial. CONCLUSION: Nearly two-thirds of our MRKH syndrome study group women with surgically created neovaginas were interested in UTx and motivated to undergo this method of absolute uterine factor infertility treatment. Therefore, this group of women might be approached to participate in ongoing and future UTx trials. Future studies of women with MRKH syndrome might confirm or disprove the results of our survey.
Keywords: Young Adult; Infertility; mladý dospělý; Attitude to Health; Adolescent; 46, XX Disorders of Sex Development; MRKH; Adult; transplantace orgánů; Prospective Studies; dospělí; laparoskopie; Organ Transplantation; Uterus; uterus; vrozené vady; mladiství; Absolute uterine factor infertility; ženská infertilita; Infertility, Female; AUFI; ductus Mülleri; lidé; ženské pohlaví; Mullerian Ducts; Humans; Neovagina; Surgically-Created Structures; postoj ke zdraví; chirurgicky vytvořené struktury; Congenital Abnormalities; Laparoscopy; Uterus transplantation; Female; Vagina; Mayer–Rokitansky–Küster–Hauser syndrome; vagina; poruchy sexuálního vývoje s karyotypem 46, XX; prospektivní studie